Serum Albumin as a Predictor of Survival after Interval Debulking Surgery for Advanced Ovarian Cancer (AOC): A Retrospective Study. Issue 2 (1st February 2022) - Dai, Dairui; Balega, Janos; Sundar, Sudha; Kehoe, Sean; Elattar, Ahmed; Phillips, Andrew; Singh, Kavita
Abstract: Objective: To investigate the impact of serum albumin (at diagnosis and pre-operatively) on survival in patients undergoing cytoreductive surgery for advanced ovarian cancer(AOC) and whether improvement in albumin achieved following neoadjuvant chemotherapy (NACT) affects overall survival (OS). Methods: Outcomes of 441 patients who underwent cytoreduction for AOC were reviewed. Albumin was recorded at diagnosis and pre-operatively. Further analysis was performed if patients were hypoalbuminaemic at diagnosis.Analysis was stratified according to whether the patientreceived primary debulking surgery (PDS) or interval debulking surgery (IDS) and if their albumin was corrected. Results: 308 patients had a serum albumin level at diagnosis and 400 patients had a pre-operative albumin available for analysis. For patients with an albumin at diagnosis ≤ 35g/L and ≥36 g/L, median OS was 31.5 (95% CI 23.5–39.5) and 50.4 (95% CI 38.9–61.9) months respectively (P = 0.003). Followingmultivariate analysis (MVA), albumin at diagnosis remained statistically significant as an independent marker for survival, even after adjusting for cytoreductive outcome, stage and grade(p = 0.04, Hazard ratio 1.38, 95% CI 1.01–1.89). Hypoalbuminaemic patients at diagnosis achieved complete cytoreduction in 53% of cases.For PDS patients, median OS was 19.7 months (95% CI 11.5–27.9). For IDS patients, median OS was 27.9 months (n = 1).IDS patients with a corrected albumin had a median OS of 42.9 months (95% CI 31.5–54.3) (p > 0.05). Conclusion: Hypoalbuminaemia at diagnosis is a poor prognostic factor in AOC. Normalization of serum albumin after NACT is a potential predictor of survival.